The Compatibility of Any Behaviour of the Price Level with Equilibrium - Gilbert, J. C. (Review of Economic Studies, 1957)
Journal Article The Compatibility of Any Behaviour of the Price Level with Equilibrium Get access J. C. Gilbert J. C. Gilbert Sheffield Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 24, Issue 3, June 1957, Pages 177–184, https://doi.org/10.2307/2296066 Published: 01 June 1957